2022
DOI: 10.1007/s40262-022-01122-5
|View full text |Cite|
|
Sign up to set email alerts
|

Hyperinflammation Reduces Midazolam Metabolism in Critically Ill Adults with COVID-19

Abstract: Background and Objective Many patients treated for COVID-19 related acute respiratory distress syndrome in the intensive care unit are sedated with the benzodiazepine midazolam. Midazolam undergoes extensive metabolism by CYP3A enzymes, which may be inhibited by hyperinflammation. Therefore, an exaggerated proinflammatory response, as often observed in COVID-19, may decrease midazolam clearance. To develop a population pharmacokinetic model for midazolam in adult intensive care unit patients infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The negative correlation between inflammation levels and drug clearance, where higher CRP or IL-6 results in lower clearance, had been observed in previous studies in this population for other drugs (midazolam, voriconazole) as well [39,40]. However, for dexamethasone the situation is even more complex since the dexamethasone itself could reduce the inflammation, so it is more difficult to distinguish the cause/ result direction.…”
Section: Discussionmentioning
confidence: 57%
“…The negative correlation between inflammation levels and drug clearance, where higher CRP or IL-6 results in lower clearance, had been observed in previous studies in this population for other drugs (midazolam, voriconazole) as well [39,40]. However, for dexamethasone the situation is even more complex since the dexamethasone itself could reduce the inflammation, so it is more difficult to distinguish the cause/ result direction.…”
Section: Discussionmentioning
confidence: 57%
“…Critically ill patients with respiratory failure due to various conditions are often managed with deep sedation for prone positioning therapy and ventilator entrainment [23]. Therefore, the dose and duration of sedation may be prolonged, leading to the prolonged action of midazolam [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…This practice has been related to a greater number of days of mechanical ventilation and episodes of delirium in ICU patients. 37,38 Several hypotheses associated with the neurotropism of the virus due to episodes of hyperexcitation and agitation have been proposed, 39 which explains the need for deep sedation in patients in the initial phases of ARDS in order to achieve protective ventilation goals. In our study we found a median dose difference between approaches of 5.7 mg/h, which compared with those who received inhaled sedation, who did not require benzodiazepines, suggests a possible decrease in these complications described; however, the reduction we found was not statistically significant in the inhaled sedation group, RR 0.8 (95% CI 0.61-1.15, P ¼ .25).…”
Section: Discussionmentioning
confidence: 99%